Isolation of CA 125 from Breast Tumor Tissue Using Gel Chromatography - Ahmed Naji, Nazar (Tikrit Journal of Pharmaceutical Sciences, 2023)
Gel filtration chromatography technique was used (Sepharose CL - 68) of CA 125 from malignant breast tumor homogenate and the isolation of (CA 125 I 1251 - anti CA 125 antibody), complex was prepared from crude CA 125 , isolated CA 125 and standard human CA 125. The results revealed the presence of two forms of CA 125 (Agl & AgII) and found to be 517 Kda and 38 Kda respectively; The isolation of CA 125 shov,:ed a purification fold of 17.5 Agl and 15 for AgII.